Demographic Characteristics of MDR TB Patients Managed with BPaLM Regimen at Raden Mattaher General Hospital Jambi Period February-September 2024 - Rizaldi, Thabina Anindya; Miranda, Melly; Justitia, Budi; Wahyudi, Dicky; Hafizah, Hafizah (Journal of Medical Studies, 2026)
Background: Multidrug-resistant tuberculosis (MDR-TB) remains a major global and national health challenge. Indonesia has implemented the new BPaLM treatment regimen, which offers a shorter duration and fewer medications compared with previous regimens, thereby aiming to improve treatment outcomes. RSUD Raden Mattaher Jambi is one of the MDR-TB referral centers in Jambi Province applying this regimen. Objective: This study aims to describe the characteristics of MDR-TB. Methods: Total sampling was used to include all MDR-TB patients who initiated BPaLM therapy from February to September 2024, resulting in 17 eligible subjects. Data were collected from medical records and the national Tuberculosis Information System (SITB). Results: The findings showed that most patients were male (82.4%) with an average age of 42 years. The majority were employed, underweight, and 52.9% had a history of smoking.  Conclusion: In conclusion, MDR-TB patients treated with the BPaLM regimen were predominantly male, of productive age, mostly employed, underweight, and had a history of smoking.